Intimate Relationship of Elderly Hajj Pilgrimages and Clotter Officers in the Aspect of Religiosity Through the Process of Self Disclosure During the Hajj - HASBIYAH, Desi; RONDA, Mirza; FAIZ, Fahruddin (PT Keberlanjutan Strategis Indonesia, 2023)
In 2023, the number of elderly Hajj pilgrims has increased significantly due to the accumulation of the Covid-19 period and priority policies. A total of 67,199 elderly Hajj pilgrims have become priority records as Hajj pilgrims who must receive special treatment. This research aims to explain, understand and discover how elderly Hajj pilgrims express themselves as individuals who are carrying out the Hajj pilgrimage and build an intimate relationship with the crew member accompanying him. The paradigm used in this research is Post Positivism with a qualitative approach using the case study method. In the research used theory is self disclosure with indicators of 5 dimensions, namely amount, valency, accuracy, Intention and Intimate and intimacy theory. The findings in this research are that self-disclosure carried out by elderly Hajj pilgrims and flight attendants forms a close, protective family relationship.